Anion Dependent Self-Assembly of Polynuclear Cd-Ln Schiff Base Nanoclusters: NIR Luminescent Sensing of Nitro Explosives - Chen, Hongfen; Yang, Xiaoping; Jiang, Weizhong; Jiang, Dongmei; Shi, Dongliang; Yuan, Bichen; Wang, Fei; Zhang, Lijie; Huang, Shaoming (Frontiers in Chemistry, 2019)
Two types of polynuclear Cd-Ln complexes [CdLnL(NO3)Cl2(DMF)2] (Ln = La (1) and Nd (2)) and [Ln2CdL2(NO3)2(DMF)2](OH)2 (Ln = La (3) and Nd (4)) were constructed using a new Schiff base ligand that has a long backbone with two phenyl groups. The Schiff base ligands show a "twist" configuration in 1-4. The crystal structures show that the molecular dimensions of 3 and 4 are about 6 × 10 × 15 Å. The Cd-Nd complexes 2 and 4 exhibit the typical NIR luminescence of Nd3+. Interestingly, 4 shows luminescent sensing of nitro explosives and exhibits high sensitivity to 2-nitrophenol at the ppm level.